Instantaneous Availability of Multi-component System under the Constraint of Spare Parts. Issue 5 (January 2021) - Wang, Yun; Hu, Pengwei; Jin, Baidong; Cheng, Hailong; Liu, Yuhan
Abstract: The availability of equipment is one of the most important indicators to measure support effectiveness of system, and spare parts supply is one of the key support resources, so it is necessary to consider the constraint of spare parts in the study of availability. As the evaluation of steady availability cannot meet the requirement of support effectiveness timely and accurately and the previous models of instantaneous availability are usually applicable to one-unit system. To solve the above problem, firstly, the whole process is divided into two sub-processes, i.e., the replace and repair process of fault system and the maintenance and turnover process of failure parts, then the influence between the two sub-processes is analysed. Secondly, a model that can compute the instantaneous availability of multi-component series system with spare parts is given. Finally, a numerical example is used to demonstrate the applicability and the performance of the proposed method.